2004
DOI: 10.3168/jds.s0022-0302(04)73435-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships Between Persistency and Reproductive Performance in First-Lactation Canadian Holsteins

Abstract: The main objective of this study was to estimate genetic relationships between lactation persistency and reproductive performance in first lactation. Relationships with day in milk at peak milk yield and estimated 305-d milk yield were also investigated. The data set contained 33,312 first-lactation Canadian Holsteins with first-parity reproductive, persistency, and productive information. Reproductive performance traits included age at first insemination, nonreturn rate at 56 d after first insemination as a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
126
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(167 citation statements)
references
References 30 publications
(65 reference statements)
31
126
9
1
Order By: Relevance
“…However, the genetic correlation between CR and milk yield in third lactation would be affected by selection for culling, because the number of cows evaluated decreased from 262 996 in first lactation to 118 820 in third lactation. Muir et al (2004) reported low positive genetic correlations between lactation persistency and NR at 56 days after first AI during first lactation in heifers and cows. Haile-Mariam et al (2003) reported near-zero genetic associations between lactation persistency and CI in first parity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the genetic correlation between CR and milk yield in third lactation would be affected by selection for culling, because the number of cows evaluated decreased from 262 996 in first lactation to 118 820 in third lactation. Muir et al (2004) reported low positive genetic correlations between lactation persistency and NR at 56 days after first AI during first lactation in heifers and cows. Haile-Mariam et al (2003) reported near-zero genetic associations between lactation persistency and CI in first parity.…”
Section: Discussionmentioning
confidence: 94%
“…This antagonistic relationship has the potential to cause serious problems if breeders select cows mainly on the basis of production traits. Muir et al (2004) suggested that factors that alter the shape of the lactation curve of an individual cow, such as lactation persistency, affect female fertility. However, few studies have focused on the genetic correlations between the CRs of cows and virgin heifers and their test-day (TD) milk yields at various stages of lactation (Veerkamp et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…If the lactation of a cow is more persistent, the lactation curve is flatter, with a lower and later peak. As a consequence, a cow with a flatter lactation curve is exposed to less stress due to high peak production, and the incidence of reproductive and metabolic disorders may be reduced to some extent (Gengler et al 1995;Muir et al 2004). Measuring lactation persistency by one single term is difficult, so persistency has been defined in many ways (Solkner and Fuchs 1987;Swalve 1994;Gengler et al 1995;Muir et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…total mixed ration) and superior genotypes. The potential to select genotypes for lactation persistency was illustrated by Muir et al (2004), who estimated lactation persistency in first lactation Canadian Holstein Friesians was moderately heritable (h 2 ¼ 0.18).…”
Section: Discussionmentioning
confidence: 99%